Study of Offensive Armament through Analytical Methods - Τσιρογιάννης, Αθανάσιος (Πανεπιστήμιο Πελοποννήσου, 2020)
In 2010,at thenorth of the modern village of Ano Melpeia, on a hilltop the ruins of an ancient building have been found and thus systematic excavations took place. Among the remnants of this building and other findings, what has also been discovered was a large number of an ancient and significant ensemble of weapons made ofiron. The aim of this thesis is to highlight the cultural value of these weapons,studying at the same time the conditions and corrosion products through SEM/EDS accompanied with optical microscopy and underlining the importance of the areathrough the following investigation.
Keywords: Όπλα, Αρχαία -- Ελλάδα -- ‘Άνω Μέλπεια (Μεσσηνία); Μεταλλοτεχνία -- Ελλάδα -- Άνω Μέλπεια (Μεσσηνία); Σίδηρος -- Ελλάδα -- Άνω Μέλπεια (Μεσσηνία) -- Ανάλυση; Σίδηρος -- Ελλάδα -- Άνω Μέλπεια (Μεσσηνία) -- Σύνθεση; Μέταλλα -- Ανάλυση; Άνω Μέλπεια (Μεσσηνία, Ελλάδα) -- Αρχαιότητες; Μεσσηνία (Ελλάδα) -- Αρχαιότητες; Irons; Weapons; Ancient; Greece; Iron; Metal; SEM; EDS; Microscopy; Armament; Ano Melpeia; Andania; Messenia; Kalamata; Archaeology; Analytical; Methods; Σιδηρά; Όπλα; Αρχαία; Ελλάδα; Σίδηρος; Μέταλλο; ΗΜΣ; ΕΔΑ; Μικροσκοπία; Εξοπλισμός; Άνω Μέλπεια; Ανδανία; Μεσσηνία; Καλαμάτα; Αρχαιολογία; Αναλυτικές; Μέθοδοι